Pengaruh Faktor Psikologis Terhadap Pengambilan Keputusan Wisatawan dalam Mengunjungi Taman Bunga Nusantara Kabupaten Cianjur - Rosiana, Eka Nuraisah; Hainim, Bem; Sadkar, Upiek Haeryah (Politeknik Pariwisata NHI Bandung, 2018)
Psychological factors are factors inherent in the individual, which will affect how the various kinds of stimuli given by marketers, will affect consumer recognition of the needs, information seeking, and a variety of alternatives before deciding to make a visit or not. This research, entitled